Unemployment, Immigration, and Populism - Shuai Chen (Institute of Labor Economics (IZA), 2023)
This paper examines how unemployment and cultural anxiety have triggered different dimensions of the current populism in the United States. Specifically, I exploit the Great Recession (GR) and the 2014 Northern Triangle immigrant influx (IM) to investigate the effects of recent unemployment and unauthorized immigration on attitudes related to populism. I find that recent unemployment during GR, rather than existing unemployment from before GR, increased the probability of attitudes against wealthy elites by 15 percentage points (PP). Such attitudes are connected with left-wing populism. I identify perceived economic unfairness as a mechanism through which recent unemployment drove left-wing populism. However, cultural anxiety rather than economic distress more likely led to the over 10 PP rise in the probability of anti-immigration attitudes during IM. These attitudes are related to right-wing populism. This study intentionally links distinct economic and cultural driving forces, respectively, to different types of populism, while still accounting for their potential interaction effects. This strategy facilitates disentangling the economic and cultural triggers of the currently surging populism.
Keywords: A13; D31; J01; J64; P16; 330; populism; unemployment; immigration; Great Recession